Learning in Adverse Circumstances: Impaired by Learning With Anxiety, Maladaptive Cognitions, and Emotions, but Supported by Self-Concept and Motivation - Paechter, Manuela; Phan-Lesti, Hellen; Ertl, Bernhard; Macher, Daniel; Malkoc, Smirna; Papousek, Ilona (Frontiers in Psychology, 2022)
The COVID-19 summer semester 2020 posed many challenges and uncertainties, quite unexpectedly and suddenly. In a sample of 314 psychology students, it was investigated how they experienced learning and preparing for an end-of-semester exam, which emotions and strain they experienced, how academic performance was affected, and how personal dispositions and attitudes as important facets of a learner’s identity could support or prevent overcoming adverse circumstances of learning. The participants of the study filled in a questionnaire about their achievement emotions and strain they experienced during learning and exam preparation as well as academic self-concept, motivation, gender, proneness to anxiety. Points achieved in the exam were also recorded. The interaction between the variables was investigated by a structural equation model. It showed that the investigated variables can be distinguished into two groups, variables that contribute mainly negatively to performance and variables with a positive contribution. Strain experienced during the COVID-19 pandemic and unpleasant emotions “belong together” in the sense that they inhibit academic performance directly or indirectly. Proneness to anxiety in academic situations was related with higher levels of mental, emotional, and physical disturbances due to the COVID-19 situation. In contrast, motivation and a high academic self-concept acted as support for learning and performance. Both contribute to pleasant achievement emotions in the learning situation; moreover, motivation had a direct relationship to academic performance. The results from the present study do not only provide insight into important students’ personal dispositions and their role for learning in adverse circumstances but also give advice how to strengthen positive dispositions for learning.